80.5k views
5 votes
Given the equation y = 4 + 2x find the values for y given the value x

If x = 3 then y=
If x = -7 then y=
If x = 1 then y=
If x= -3 then y=

User XandrUu
by
4.9k points

2 Answers

3 votes

Answer:

10, - 10, 6, - 2

Explanation:

Substitute each given value of x into the expression and evaluate.

x = 3 → y = 4 + 2(3) = 4 + 6 = 10

x = - 7 → y = 4 + 2(- 7) = 4 - 14 = - 10

x = 1 → y = 4 + 2(1) = 4 + 2 = 6

x = - 3 → y = 4 + 2(- 3) = 4 - 6 = - 2

User Cavalcade
by
5.2k points
5 votes

Answer:

1. y= 10 2.y= -10 3.y= 6 4.y= -2

Explanation:

You basically just replace x with the number.

So, for y = 4 + 2x, then replace x with 3 and go y = 4 + 2(3)

which translates to y = 4 + 6 which equals 10

User Learningbyexample
by
5.2k points